Linguistic Trends and Foreign Language Teaching: The Case of French - Umoh, Daniel Effiong (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Linguistics is generally defined as the scientific study of human language. Whereas language is considered as an instrument of communication through which human experience is analyzed differently. Meanwhile, the spread of linguistics theories is propelled by the desire to find better ways to learn and acquire foreign languages, such as French. Hence, in what ways have the development of linguistics theories contributed to language learning and acquisition? An attempt to answer this question was made and some linguistic theories were explained.